The Gorbachev Anti-Alcohol Campaign and Russia's mortality crisis - Bhattacharya, Jay; Gathmann, Christina; Miller, Grant (Discussion paper series, 2012)
Political and economic transition is often blamed for Russia's 40% surge in deaths between 1990 and 1994 (the "Russian Mortality Crisis"). Highlighting that increases in mortality occurred primarily among alcohol related causes and among working-age men (the heaviest drinkers), this paper investigates an alternative explanation: the demise of the 1985-1988 Gorbachev Anti-Alcohol Campaign. We use archival sources to build a new oblast-year data set spanning 1970-2000 and find that: (1) The campaign was associated with substantially fewer campaign year deaths, (2) Oblasts with larger reductions in alcohol consumption and mortality during the campaign experienced larger transition era increases, and (3) Other former Soviet states and Eastern European countries exhibit similar mortality patterns commensurate with their campaign exposure. The campaign's end explains a large share of the mortality crisis, suggesting that Russia's transition to capitalism and democracy was not as lethal as commonly suggested. -- mortality ; transition ; alcohol ; Russia
Keywords: 1970-2000; Arbeitspapier; Graue Literatur